Two‐Dimensional NMR Spectroscopy with Temperature‐Sweep. Issue 11 (26th May 2014) - Bermel, Wolfgang; Dass, Rupashree; Neidig, Klaus‐Peter; Kazimierczuk, Krzysztof
Abstract Two‐dimensional nuclear magnetic resonance (NMR) spectroscopy is useful for studying temperature‐dependent effects on molecular structure. However, experimental time is usually long, because sampling is repeated at several temperatures. A novel solution to the problem is proposed, in which signal sampling is performed in parallel to the linear temperature‐sweep.